Kinetic mechanisms of the pelvis rotation about its longitudinal axis during the golf swing - Takagi, T.; Murata, M.; Yokozawa, T. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to clarify the dynamics of the pelvis axis rotation during the golf swing. Sixteen skilled golfers performed swings with the driver. The 3D kinematic data and ground reaction forces were collected using an optical motion analysis system and two force platforms. The dynamic components of the pelvis angular acceleration were calculated as a function of 1) joint torque, 2) gravity, 3) motion-dependent forces, and 4) inertia force parameters. The present study found that the joint torque was the largest component of the pelvis axis rotation. In the torque component, both hip joint torques about its extension/flexion and adduction/abduction axes most affect the pelvis axis rotation, but the role of the torques differs between the rear and target legs. The control strategy of the pelvis axis rotation during the golf swing was discussed